DNA Profiles of Salmonella Spp. Isolated from Chicken Products and From Broiler and Human Feces - Tejada,TS (2016)
ABSTRACT Salmonella species have been isolated from various kinds of food and are accountable for outbreaks of foodborne diseases in humans. This study aimed at identifying the similarities between the DNA profiles of Salmonella isolated from chicken feces, chicken products, and human feces in southern Brazil. Six hundred samples were collected (200 from chicken products, 200 from broiler chicken feces, and 200 from human feces) and tested for the presence of Salmonella. Isolates proven to be Salmonella compatible by biochemical and serological tests were tested by the Polymerase Chain Reaction. Their DNA profiles were then analyzed by PFGE and rep-PCR. Salmonella was isolated from 16 out of 600 analyzed samples, with Schwarzengrund serotype presenting the highest incidence, followed by Mbandaka in chicken meat and fecal samples, and Panama in human fecal samples. Some strains isolated from chicken fecal and product samples were indistinguishable by the molecular methods used in the study, suggesting that that the contamination of the broilers on the farm can be transmitted the processed products.